Sequential coupling of electromagnetic–structural simulation for compression welding of tubular jobs. (May 2019) - Khan, Mohammed Rajik; Hossain, Md. Mosarraf; Sharma, Archana; Kumar, Satendra
This work adopts a simplified analytical approach to design an axi-symmetric bitter circular coil and presents a sequential-coupled simulation of electromagnetic welding for tubular jobs using finite element analysis. A three-dimensional axi-symmetric transient electromagnetic model is proposed to predict the developed magnetic field and pressure, which is sequentially coupled to the mechanical model to obtain the deformations occurring on the mating members. Results in the form of changes in impact velocity, shear stress, and effective plastic strain induced on the outer wall of the flyer tube with varying process parameters, via input voltage and initial angle of taper of inner solid plug during welding simulation are graphically shown. Based on the results of the coupled finite element simulation, a weldability window for effective welding of tubular jobs is proposed.